KINETIC STUDY OF PHOSPHOR DAN NITROGEN COMPOUNDS FROM SEDIMENTARY RE-SUSPENSION - T. Prartono; T. Hasena (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2009)
Kinetic study of phosphor and nitrogen compounds through resuspension sediment has been carried out to determine their time release from sediment to the water column. This laboratory study was performed by stirring the sediment within the seawater at an equal current speed of 1 m/sec. Nutrients were observed at several intervals of 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes and 40 minutes by sampling 25 ml water mixture with 3 time as replicates. The increase of nutrient occurred significantly during 5 minutes. Their average contribution of nutrient per gram sediment reached 1.827 μg phosphate, 0.292 mg ammonia, 0.276 mg ammonium, 1.776 μg nitrite and 9.059 μg nitrate. The extent of nutrient increase was probably depended upon characteristic of sediment (composition of nutrient availability) and resuspension speed.Keywords: kinetic, nutrient, resuspension, sediment, Jakarta Bay.